Al-Rahnu implementation: comparative study between Bank Rakyat and YAPEIM / Shazriliz Ariza Rosli. - Rosli, Shazriliz Ariza (2019)
Al-Rahnu is an Islamic pawnbroking system that is fully utilized by low-income groups to obtain financial resources in the short term. The purpose of this research is to study the implementation of Al-Rahnu in both institutions – YaPEIM and Bank Rakyat and to compare the procedures and acceptance of the community to their products. Problems and challenges were also discussed in this study to identify the problems faced and solutions made by Islamic mortagage institutions during the operational. The improvement measures undertaken by Islamic mortgage institutions (Al-Rahnu) to introduce and promote the use of Islamic pawnshops are discussed in this paper. The research has used data collection methods through interviews and observations on the two institutions where an interview session was made with two respondents to obtain accurate information about the Al-Rahnu product. The findings show that there is little difference in the implementation of Al-Rahnu in both institutions but does not affect the customers to choose between preferred Islamic mortgage institutions. The result from this research shows that Al-Rahnu gets a lot of positive impact from customers day by day.